2008
DOI: 10.1016/j.neuropharm.2008.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the level of OFQ/N-IR in rat brain regions by cocaine

Abstract: We have previously shown that administration of orphanin FQ/nociceptin (OFQ/N), the endogenous ligand of the opioid receptor-like (ORL-1) receptor, into the lateral ventricles or VTA blocked cocaine sensitization. In the present study, we determined the effect of acute and chronic cocaine treatment on the level of endogenous OFQ/N in rat brain regions. Male Sprague Dawley rats were tested for motor activity in response to saline or cocaine (20 mg/kg) injection once daily for three consecutive days. To determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 59 publications
(63 reference statements)
2
10
0
Order By: Relevance
“…These intriguing results imply that neuronal adaptive changes may occur along the OFQ/N/ORL-1 receptor system following repeated cocaine treatment. Consistent with this notion, we have previously shown that the level of OFQ/N was increased in the hippocampus of rats sensitized to cocaine (45). Thus, further research is needed to elucidate the underlying mechanisms of these neuronal and behavioral adaptive changes in the OFQ/N/ORL-1 receptor system following repeated cocaine treatment.…”
Section: Discussionsupporting
confidence: 76%
“…These intriguing results imply that neuronal adaptive changes may occur along the OFQ/N/ORL-1 receptor system following repeated cocaine treatment. Consistent with this notion, we have previously shown that the level of OFQ/N was increased in the hippocampus of rats sensitized to cocaine (45). Thus, further research is needed to elucidate the underlying mechanisms of these neuronal and behavioral adaptive changes in the OFQ/N/ORL-1 receptor system following repeated cocaine treatment.…”
Section: Discussionsupporting
confidence: 76%
“…Interestingly, however, the level of OFQ/N-IR was found to be increased in the hippocampus of rats that received repeated intermittent cocaine treatment and showed locomotor sensitization. 71 These results suggest that the endogenous OFQ/N may be involved in the acute and chronic actions of cocaine.…”
Section: Orphanin Fq/nociceptin/nopr Systemmentioning
confidence: 87%
“…Reductions were also seen in the striatum and prefrontal cortex but these changes were not significantly different from the saline-treated controls. 71 However, tissue content does not provide information about the release, metabolism, and/or synthesis of the peptide. Additionally, given that these changes were measured 1 h after cocaine administration, future studies using microdialysis in freely moving animals are needed to assess the dose–-response and time course effect of single and repeated cocaine administration on the release of endogenous OFQ/N.…”
Section: Orphanin Fq/nociceptin/nopr Systemmentioning
confidence: 99%
“…For example, acute ethanol administration increases NOP receptor density in cortical areas, whereas acute administration of cocaine does not (Rosin et al, 2003). Furthermore, under chronic treatment conditions, alcohol administration decreases N/OFQ brain tissue levels (Lindholm et al, 2002), whereas repeated cocaine administration increases N/OFQ immunoreactivity in the brain (Lutfy et al, 2008). …”
Section: Nociceptin/orphanin Fqmentioning
confidence: 99%